Sanitation and Hygiene in Africa: Where do we Stand? - Cross, Piers (IWA Publishing, 2013)
"The Third African Sanitation and Hygiene Conference was held in Kigali, Rwanda in July 2011. It was hosted by the Government of the Republic of Rwanda, and the African Minister s Council on Water. The meeting attracted extraordinary interest: over 1000 people registered and nearly 900 people attended from a total of 67 countries, including representatives of 42 African countries. The content of AfricaSan 3 was aligned with the needs of countries as defined in country preparation meetings which took place in advance. AfricaSan 3 looked to address the country needs and to commitments and country action planning. Different groups (ministers, civil society, local government, utilities, and donors) committed to actions to support the goals of AfricaSan. The goal of the AfricaSan process is to support countries to achieve the Millennium Development Goal, (MDG) for sanitation and hygiene. Sanitation and Hygiene in Africa: Where do We Stand? takes stock of progress made by African countries through the AfricaSan process since 2008 and the progress needed to meet the MDG on sanitation by 2015 and beyond. This book addresses priorities which have been identified by African countries as the key elements which need to be addressed in order to accelerate progress. -- Reviews progress on implementing the eThekwini Declaration to meet the MDG for sanitation and progress generally in Africa. It analyses what is needed to accelerate the rate of access to sanitation in Africa. -- Shares advances in the evidence base on sanitation and hygiene in Africa to be able to assist decision-makers to overcome key blockages in implementing large-scale sanitation and hygiene programs. -- Raises the profile of sanitation and hygiene as a determinant of sustainable development in order to strengthen leadership and advocacy for sustained sanitation and behavior changes. This book is essential reading for government staff from Ministries responsible for sanitation, sector stakeholders working in NGOs, CSOs and agencies with a focus on sanitation and hygiene and water and sanitation specialists. It is also suitable for Masters courses in water and sanitation and for researchers and the donor community."